Pengaruh Penerapan IFRS, Jenis Industri dan Probabilitas Kebangkrutan terhadap Audit Delay (Pada Perusahaan LQ 45 yang Terdaftar di Bursa Efek Indonesia Periode 2013-2015) - Ina Amalia Nurahmayani; Pupung Purnamasari; Magnaz Lestira Oktaroza (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2018)
The delay audit is the period in completing the audit process by an independent auditor from the closing date of the book on 31 December until the date of signing of the independent auditor's report. Audit delay can occur because of obstacles in the implementation of the audit process. This study aims to obtain empirical evidence on the effect of IFRS implementation, industry type, and bankruptcy probability of audit delay. The research method used in this research is descriptive analysis method and quantitative method by using multiple regression analysis. This research uses sample data of LQ 45 index company that listed in Bursa Efek Indonesia (BEI) during period 2013-2015. Sampling method used is purposive sampling method. After selecting based on purposive sampling method, there are 14 LQ 45 index companies that meet the required sample criteria with observation period for 3 years, so that 42 observations are obtained. The results of this study indicate that the implementation of IFRS effect on audit delay, Industrial Type affect audit delay, Probability Bankruptcy does not affect audit delay. The researcher recommends for further research to use other sector companies for research, using a method of determining samples other than purvosive sampling, replacing other independent variables that may affect audit delay.